Conformal radiotherapy as a bridge to liver transplantation for hepatocellular carcinoma: is it safe?. (July 2016) - Mohkam, Kayvan; Golse, Nicolas; Bonal, Mathieu; Ledochowski, Stanislas; Rode, Agnès; Selmaji, Imad E; Merle, Philippe; Ducerf, Christian; Mornex, Françoise; Mabrut, Jean-Yves
Aim: To report a preliminary experience of conformal radiotherapy (CRT) as bridge to orthotopic liver transplantation (OLT) for hepatocellular carcinoma (HCC).Methods: Data of 12 patients undergoing CRT for HCC followed by OLT between 2012 and 2014 were reviewed.Results: CRT was used in a neoadjuvant or downstaging setting in nine and three patients, respectively. No radiation-related systemic toxicity was observed. Median blood loss and operating time were 1450 ml (600–4000) and 420 min (240–510), respectively. Four patients had diaphragmatic injury. Complete histological response was observed in six patients, and partial response in five. Seven patients developed severe postoperative morbidity including five anastomosis-related complications and one death.Conclusion: CRT for HCC provides satisfactory histological response but may compromise OLT safety.